Legal Protection For Children As Victims Used As Narcotics Couriers - Lubis, Pangiutan Tondi (Inspiring Law Journal, 2024)
Law Number 35 of 2009 concerning Narcotics, explains in general about criminal sanctions for drug intermediaries (couriers) but does not specifically regulate criminal sanctions for children who become drug couriers. However, basically, perpetrators of drug trafficking involving children as drug couriers are still subject to the articles as regulated in the Narcotics Law but without ignoring the special provisions regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Diversion can only be implemented for crimes with a prison sentence of less than 7 (seven) years. Legal treatment for minors in drug trafficking cases should receive serious attention. Law enforcers and those processing and deciding must be sure that the decisions taken will be a strong basis for returning and managing children towards a good future to develop themselves as citizens who are responsible for the life of the nation